Typography, referenced : a comprehensive visual guide to the language, history, and practice of typography / Allan Haley [and others] - Haley, Allan (Rockport Publishers, 2012)
This is the ultimate reference on typographic history, design, and practice within the past thirteen years. It includes type terminology, typefaces, type design and development, principles of typography and classification, significant type designers--past and present--type foundries and much more all fully illustrated. Written by experts in the field, this is the most comprehensive and up-to-date volume on the subject of typography.